Advanced glycation end-products in senile diabetic and non-diabetic patients with cardiovascular complications - Gul, Anjuman (Springer Netherlands, 2008)
Advanced glycation end products (AGEs) have been reported to contribute to aging and cardiovascular complications. In the present study, the immunoreactivity of AGEs in human serum samples of healthy older subjects (n = 31), senile diabetic patients without cardiovascular complications (n = 33), senile diabetic patients with cardiovascular complications (n = 32), senile non-diabetic patients with cardiovascular complications (n = 30) ,and healthy young subjects (n = 31) were investigated. The patients were selected on clinical grounds from the National Institute of Cardiovascular Disease, Karachi and the Jinnah Postgraduate Medical Centre, Karachi, Pakistan. Fasting blood glucose, HbA(1C) and serum fructosamine levels were significantly (P < 0.001) increased in senile diabetic patients with and without cardiovascular complications as compared to non-diabetic senile patients with cardiovascular complications and healthy older subjects. Additionally, serum AGEs were found to be significantly (P < 0.001) increased in senile diabetic patients with cardiovascular complications and senile non-diabetic patients with cardiovascular complications, followed by diabetic patients without cardiovascular complications as compared to healthy older subjects and young control subjects. However, no significant difference was found in the senile diabetic patients without cardiovascular complications and senile non-diabetic patients with cardiovascular complications. In contrast to all four senile groups, serum AGEs were significantly (P < 0.001) lower in young control subjects. The AGEs distribution in the senile groups corroborates the hypothesis that the advanced glycation process might play a role in the development of cardiovascular complications, which are more severe in diabetic patients compared with non-diabetic patients with cardiovascular complications.